Analysis of Mosque Financial Management to Optimization the Role of Mosque in Advancing Communities Using Critical Ethnomethodology Studies - Sugiharto; Dewi Kirowati; Vaisal Amir (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2019)
The purpose of this study is to see the extent of mosque financial management to optimize the role of the mosque in advancing the surrounding community both in terms of religious, economic, social, and cultural. In addition, this study also aims to see the extent of the influence of the mosque in the formation of community character in the environment around the mosque. This research focuses on governance carried out by the management, including leadership and management of the resources they have in advancing economic, social, cultural life and shaping the character of a more religious society. The method used in this research is qualitative non-positivistic, using a critical ethnomethodology analysis tool. Primary data in this study were obtained through in-depth interviews and direct observation. While secondary data in the study were obtained by looking at the records held by the manager as well as other data related to the research object. The expected outcome is the identification of problems with the financial management of the existing mosque and the resolution of the problem with the aim of optimizing the role of the mosque in building and advancing the community around the main mosque in facing the modern era as it is today. In addition, the results of this study will also be an input and reference for the mosque's financial management that is independent and has an impact on the progress and prosperity of the community (both physically and mentally).